The association of microcephaly protein WDR62 with CPAP/IFT88 is required for cilia formation and neocortical development. (9th December 2019) - Shohayeb, Belal; Ho, Uda; Yeap, Yvonne Y; Parton, Robert G; Millard, S Sean; Xu, Zhiheng; Piper, Michael; Ng, Dominic C H
Abstract: WDR62 mutations that result in protein loss, truncation or single amino-acid substitutions are causative for human microcephaly, indicating critical roles in cell expansion required for brain development. WDR62 missense mutations that retain protein expression represent partial loss-of-function mutants that may therefore provide specific insights into radial glial cell processes critical for brain growth. Here we utilized CRISPR/Cas9 approaches to generate three strains of WDR62 mutant mice; WDR62 V66M/V66M and WDR62 R439H/R439H mice recapitulate conserved missense mutations found in humans with microcephaly, with the third strain being a null allele (WDR62 stop/stop ). Each of these mutations resulted in embryonic lethality to varying degrees and gross morphological defects consistent with ciliopathies (dwarfism, anophthalmia and microcephaly). We find that WDR62 mutant proteins (V66M and R439H) localize to the basal body but fail to recruit CPAP. As a consequence, we observe deficient recruitment of IFT88, a protein that is required for cilia formation. This underpins the maintenance of radial glia as WDR62 mutations caused premature differentiation of radial glia resulting in reduced generation of neurons and cortical thinning. These findings highlight the important role of the primary cilium in neocortical expansion and implicate ciliary dysfunction as underlying the pathology of MCPH2 patients.